2012
DOI: 10.1002/jor.22302
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of thrombospondin‐2 accelerates ischemic fracture healing

Abstract: Thrombospondin-2 (TSP2) is a matricellular protein that is highly up-regulated during fracture healing. TSP2 negatively regulates vascularity, vascular reperfusion following ischemia, and cutaneous wound healing. As well, TSP2-null mice show increased endocortical bone formation due to an enhanced number of mesenchymal progenitor cells and show increased cortical thickness. Mice deficient in TSP2 (TSP2-null) show an alteration in fracture healing, that is unrelated to their cortical bone phenotype, which is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…The predicted pattern of healing in the model of mildly impaired angiogenesis was similar to that observed experimentally during ischemic fracture healing by Miedel et al (Miedel et al, 2013), while the pattern of healing predicted in the models of moderately and severely impaired angiogenesis was similar to the ex- perimental observations of Lu et al (Lu et al, 2007). In their study, Miedel et al (Miedel et al, 2013) found that, although ischemia during fracture healing resulted in delayed healing, by day 20, bony union between the cortical surfaces had been achieved. This behaviour was observed in the model of mild vascular impairment whereby bridging of the fracture gap had occurred by day 21.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The predicted pattern of healing in the model of mildly impaired angiogenesis was similar to that observed experimentally during ischemic fracture healing by Miedel et al (Miedel et al, 2013), while the pattern of healing predicted in the models of moderately and severely impaired angiogenesis was similar to the ex- perimental observations of Lu et al (Lu et al, 2007). In their study, Miedel et al (Miedel et al, 2013) found that, although ischemia during fracture healing resulted in delayed healing, by day 20, bony union between the cortical surfaces had been achieved. This behaviour was observed in the model of mild vascular impairment whereby bridging of the fracture gap had occurred by day 21.…”
Section: Discussionsupporting
confidence: 85%
“…The developed models of ischemia also provide a potential explanation for the conflicting results reported by studies examining the pattern of healing within fractured ischemic limbs (Miedel et al, 2013;Lu et al, 2007). The predicted pattern of healing in the model of mildly impaired angiogenesis was similar to that observed experimentally during ischemic fracture healing by Miedel et al (Miedel et al, 2013), while the pattern of healing predicted in the models of moderately and severely impaired angiogenesis was similar to the ex- perimental observations of Lu et al (Lu et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations